Drifting into politics the unfinished memoirs of Tun Dr. Ismail Abdul Rahman - Ismail Tun 1915-1973
This is the unfinished autobiography of Tun Dr Ismail Abdul Rahman, the medical doctor who held key government positions in the first two decades of Malaysian nation building, and who was an important early player within UMNO, the country's dominant political party.